Managing Interdisciplinary, Longitudinal Research Teams: Extending Grounded Theory-Building Methodologies - O'Connor, Gina Colarelli; Rice, Mark P; Peters, Lois; Veryzer, Robert W (Organization science (Providence, R.I.), 2003)
The purpose of this study is to extend the literature on grounded theory development to incorporate considerations for teambased, interdisciplinary longitudinal research projects in the domain of organizational studies. Every element of the research process is affected if the research questions call for teambased data collection and interpretation over a lengthy period of time. It is unusual for a team of scholars from different disciplines to work together, not because the need doesn't exist, but because the mechanisms for doing so are not well established. We draw from the writings of scholars in the fields of research methodology, team and workgroup design, and project management to inform our thinking on the subject. The work presented here is based on the authors' experiences during 19951999 as members of the Radical Innovation Research Program (RIRP). The RIRP is an ongoing multidisciplinary study of the development and management of radical innovations in established firms. Here, we do not describe the findings or insights associated with the content of the study, radical innovation, which is surely a complex managerial phenomenon. Rather, we focus on the processes used to conduct the research that were affected by the need for a multidisciplinary research team. A framework is presented for thinking about managing such a project. Challenges that we encountered within this framework are identified. Mechanisms we used (or, in some cases, wish we had used in retrospect) for confronting those challenges are also described. Throughout, we compare our study objectives and resultant methodological design choices with those of other multidisciplinary research teams that are by now well known in the organizational management literature. Our objective is to help researchers who are considering launching interdisciplinary, longitudinal studies of organizational processes as they plan and manage those pursuits.